Changes in the prevalence of causative pathogens isolated from severe burn patients from 2012 to 2017. Issue 3 (May 2020) - Park, Jin Ju; Seo, Yu Bin; Choi, Young Kyun; Kym, Dohern; Lee, Jacob
Highlights: Bloodstream infection samples from burn patients were evaluated. The multidrug-resistant bacteremia appeared from the earliest phase of hospitalization. The proportion of CRE increased by the length of hospital stay. Abstract: Infection is the leading cause of mortality in severe burn patients, benefitting from periodic monitoring of changes in bacterial prevalence and antibiotic resistance trends. This single facility retrospective study evaluated blood culture results for patients hospitalized in the burn intensive care unit (BICU) from January 2012 to December 2017. A total of 969 samples from 420 patients were reviewed. Isolated pathogens were recorded by year and the number of days of hospitalization. Results showed that Acinetobacter baumanni was the most predominant isolated pathogen, followed closely by Pseudomonas aeruginosa, Klebsiella spp., and Enterococcus spp. Throughout this 6-year study, several significant trends were noted; Klebsiella species increased, while P. aeruginosa decreased. Staphylococcus aureus and Klebsiella species gradually increased, and P. aeruginosa doubled as the length of hospital stay increased to 22 days. Interestingly, as the length of the hospital stay increased, the proportion of Carbapenem-resistant Enterobacteriaceae (CRE) significantly increased up to 45.0% at 22 days ( P = 0.003). Conversely, the proportion of Acinetobacter baumannii gradually decreased as the days hospitalized increased. Overall, the rate of multidrug-resistant (MDR) bacteremia found in burn patients was substantially higher than that in other patients and appeared from the earliest phase of hospitalization. Therefore, early use of antibiotics targeting MDR Gram-negative bacteria in burn patients admitted to the BICU might be warranted. Further, since CRE infections increase in abundance over time, significant effort should be made to manage the initial CRE infections of burn patients before they can multiply into a life-threatening situation.